Longitudinal formative interventions in the Elkonin – Davydov’s context - Galina Zuckerman (Problemy Wczesnej Edukacji)
The paper presents the historical description of the development of D.B. Elkonin and V.V. Davydov’s original educational system and the fundamental components of the genetic modeling experiment in this system. The history of the Elkonin-Davydov laboratory is seen as a series of macrocycles of genetic modeling experiments. Each cycle once begun, has been going on through the following decades.